Positive effect of pedometer-based walking intervention on body image and physical activity enjoyment in adolescent girls - Kantanista Adam; Bronikowski Michał; Laudańska-Krzemińska Ida; Król-Zielińska Magdalena; Osiński Wiesław (Sciendo, 2017)
Study aim: To assess the effects of an eight-week pedometer-based walking intervention, using different strategies of goalsetting, on self-efficacy, physical activity enjoyment, and body image.